A Comparison of Surgical and Medical Treatment of Fragmented Coronoid Process and Osteochondritis Dissecans of the Canine Elbow - Bouck, G. R.; Miller, C. W.; Taves, C. L. (Veterinary and Comparative Orthopaedics and Traumatology, 1995)
A randomized prospective clinical study was performed to compare the effect of surgery for fragmented coronoid process (FCP) and osteochondritis dissecans (OCD) of the canine elbow, with medical treatment using pentosan polysulphate (PPS). Nineteen dogs with FCP and/or OCD of the elbow were randomly assigned to either the surgical or medical group. Lameness examination, radiographic evaluation and force plate analysis were performed at the time of admission, and were repeated at two, four, six and nine months after treatment. In dogs with asymmetrical lameness, in both the medical and surgical groups, the peak vertical forces and mean vertical forces for the more affected limbs were significantly lower than the control means at time zero. In both the medical and surgical group, the peak and mean vertical forces improved during the course of the study. Weightbearing in medically treated dogs approached that in controls at a faster rate than in those treated surgically. After nine months of follow-up, differences could not be detected between the dogs treated surgically, and those treated with PPS.Surgical and medical treatment for fragmented coronoid process and osteochondritis dissecans of the canine elbow were compared. Medical treatment resulted in a more rapid return to normal weight-bearing than did surgical treatment. After nine months of follow-up, differences were not detected between the medically and surgically treated dogs.
Keywords: Fragmented coronoid process; osteochondritis dissecans; pentosan polysulphate; force plate analysis